1994
DOI: 10.1002/jbm.820281209
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization and pH relationships in healing skeletal defects grafted with demineralized bone matrix

Abstract: Early studies had indicated that tissue repair is initially associated with a lower than normal serum pH that later becomes more alkaline. To determine how tissue pH may affect skeletal healing and mineralization, we used a rat skeletal repair model consisting of a long bone segmental defect grafted with acid-demineralized bone matrix (DBM), a biomaterial possessing both osteoinductive and osteoconductive repair properties. In this study, femoral and tibial diaphyses from young adult Sprague Dawley rats were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 13 publications
2
62
0
Order By: Relevance
“…22,23,32 Likewise, the osteogenic capacity of BMSCs also varies depending on the culture environment. 10,[38][39][40] On the basis of the results of this study, it is clear that small shifts in extracellular pH lead to significant changes in the ability of BMSCs to express markers of the osteoblast phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23,32 Likewise, the osteogenic capacity of BMSCs also varies depending on the culture environment. 10,[38][39][40] On the basis of the results of this study, it is clear that small shifts in extracellular pH lead to significant changes in the ability of BMSCs to express markers of the osteoblast phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…23,25,26 Therefore, it has been suggested that mineralization and bone repair are tissue pH dependent. 23 On a cellular level, even modest reductions in extracellular pH have an effect on osteoblast function in vitro. 27,28 Cellular mechanisms involved in bone formation and resorption may therefore be responsive to the acid-base balance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acid tide of wound healing, i.e., the pH within wounds and fractures, change from acidic to neutral and alkaline pH as the healing process progress (18)(19)(20)(21)(22)(23)(24). The local environment is acidic during the initial stage of healing.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has also been described that mineralization and bone repair is pH dependent. The early acidity within fracture hematomas is later followed by a change in pH towards alkalinity (19)(20)(21)(22)(23)(24). A low pH has also been reported during the early phase of wound healing, hence designated the acid tide (25).…”
Section: Introductionmentioning
confidence: 99%